Phytochemical screening, cytotoxicity and anticancer activity of Lobostemon fruticosus extracts on human lung cancer cell line - Ndlovu, Lungile Melly (My University, 2015)
Lung cancer is currently the most deadly form of cancer due to the fact that metastasis occurs in the lymph nodes making it difficult to remove by surgical means. Chemotherapy has been the most successful method of treatment, although it has been harmful to human health as a consequence of non-specific cytotoxicity. There has been, therefore, a growing interest in cancer research to develop alternative cancer treatments, which are less toxic. Currently plant-derived drugs are perceived to be more effective as they display both cytotoxic activity and are less harmful to overall human health. Thus the aim of the study was to determine the cytotoxic effects of the plant Lobostemon fruticosus on A549 cells. The IC50 of the methanol and butanol extracts of L. fruticosus were obtained at 40 μg/ml and 50 μg/ml, respectively. DNA fragmentation was observed after 48 hour exposure to treatments, indicating that the plant extracts induced apoptosis. Cell cycle analysis indicated that the plant extracts inhibited cell cycle progression at the sub-G0 phase, which indicated that the cells had undergone apoptosis. RT-PCR showed that the expression of p53 was down-regulated; however, p21 and Bax were up-regulated in all treatments. LC-MS identified that the compounds from the plant extracts are known apoptotic inducers. The results lead to the conclusion that the extracts of L. fruticosus, induce cell death in A549 cells. The plant extracts induced a p53-independent apoptotic mechanism, which was mediated by Bax and p21. Key words: Lobostemon fruticosus, camptothecin, taxol, Non-small cell lung cancer (NSCLC)
A dissertation submitted to the Faculty of Science, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. March 2015
Keywords: Lobostemon fruticosus.; Camptothecin.; Taxol.; Non-small cell lung cancer (NSCLC); Lungs--Cancer.; Apoptosis.; Cell-mediated cytotoxicity.; Cancer--Chemotherapy.